The Role of Bhabinkamtibmas in Utilizing WhatsApp Application Counseling to Prevent Domestic Violence in Blitar City Police Resort - Sutrisno, Agung Wira Nugraha (Advances in Police Science Research Journal, 2024)
The background of this issue arises due to the increasing reports of domestic violence in the jurisdiction of the Blitar City Police Resort. With the advancement of technology to facilitate communication, it should be able to reduce the incidence of Domestic Violence. The aims of this research to understand the utilization of WhatsApp as a supporting medium for problem-solving and report acceptance from Bhayangkara pembinaan keamanan dan ketertiban masyarakat (Bhabinkamtibmas) in the jurisdiction of the Blitar City Police Resort. The theories used to analyze the research focus are Management Theory, SWOT Theory, Cooperation Theory, and Human Resources Theory. The concepts utilized include Utilization concept, WhatsApp concept, Bhabinkamtibmas concept, and Domestic Violence concept. This research employs a qualitative descriptive studies with Field Research as the research type. Data collection techniques include interviews, observations, and document studies. Data validity is ensured through data triangulation involving source, technique, time, and theory triangulation. The research findings indicate that the utilization of WhatsApp media by Bhabinkamtibmas is not yet optimal. There are still constraints faced by members due to their suboptimal communication with victims or reporters and the lack of proficiency of Bhabinkamtibmas members when dealing with the community in problem-solving. Thus, the active involvement of Bhabinkamtibmas on WhatsApp media to communicate with the Blitar City community is necessary. In conclusion, the utilization of WhatsApp as a supporting medium to reduce the incidence of Domestic Violence by Bhabinkamtibmas is not yet optimal. Recommendations include providing training for Bhabinkamtibmas in social media communication, creating engaging educational materials, rotating the responsibility within the Binmas unit, and proposing Standard Operating Procedures for WhatsApp media usage in Bhabinkamtibmas tasks execution.